Sistem Informasi Pelayanan Publik Pada Kelurahan Jurangmangu Barat - Mohamad Firmansyah; Rinna Rachmatika (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Jurangmangu Barat sub-district is a sub-district in the Pondok Aren district of South Tangerang City, Banten Province. Currently, in its implementation, Jurangmangu Barat sub-district still uses conventional services to serve the residents, and for obtaining information, the sub-district relies on information from the district administration, which is still quite rigid. Therefore, Jurangmangu Barat sub-district needs a website-based information system that encompasses the overall profile of the sub-district, sub-district monographs, and public services that can be accessed through a single website. This information system aims to obtain and provide information that is not too rigid. With the implementation of this public service information system, the sub-district can manage services and obtain information through just one website. The purpose of developing this information system is to facilitate both the sub-district administration and the residents in obtaining information and streamlining the service process.